Highly Efficient Indium Tin Oxide-free Organic Photovoltaics Using Inkjet-printed Silver Nanoparticle Current Collecting Grids - Hermerschmidt, Felix; Savva, Achilleas; Georgiou, Efthymios; Choulis, Stelios A.; Neophytou, Marios (My University, 2012)
We report an in-depth investigation of an inkjet-printed silver (Ag) nanoparticle grid combined with poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) of different conductivities as an alternative to an indium tin oxide (ITO)-based transparent anode for organic solar cell applications. The reported measurements revealed higher transparency of the inkjet-printed Ag nanoparticle-based grid when compared to different thicknesses of ITO on glass substrates. Based on the proposed current collecting grid, a record power conversion efficiency of 2% is achieved for ITO-free organic solar cells
Keywords: Photovoltaics; Solar cells; Nanoparticles